Immunomodulatory drugs in AL amyloidosis - Jelinek, T; Kufova, Z; Hajek, R (Critical reviews in oncology/hematology, 2016)
Immunoglobulin light chain amyloidosis (AL amyloidosis) is indeed a rare plasma cell disorder, yet the most common of the systemic amyloidoses. The choice of adequate treatment modality is complicated and depends dominantly on the risk stratification of these fragile patients. Immunomodulatory drugs (IMiDs) are currently used in newly diagnosed patients as well as in salvage therapy in relapsed/refractory patients. IMiDs have a pleiotropic effect on malignant cells and the exact mechanism of their action has been described recently. Thalidomide is the most ancient representative, effective but toxic. Lenalidomide seems to be more effective, nevertheless the toxicity remains high, especially in patients with renal insufficiency. Pomalidomide is the newest IMiD used in this indication with a good balance between efficacy and tolerable toxicity and represents the most promising compound. This review is focused on the evaluation of all three representatives of IMiDs and their roles in the treatment of this malignant disorder.
Keywords: Thalidomide; Amyloidosis; lehké řetězce imunoglobulinů; Humans; Immunoglobulin Light Chains; Immunomodulatory drugs; lidé; zvířata; záchranná terapie; Salvage Therapy; amyloidóza; imunologické faktory; Lenalidomide; AL amyloidosis; Immunologic Factors; Animals; Pomalidomide; lenalidomid; thalidomid